2015
DOI: 10.1007/s00216-015-8559-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative profiling of endocannabinoids in lipoproteins by LC–MS/MS

Abstract: Endocannabinoids belong to a diverse family of endogenous lipid bioregulators acting as physiological ligands of cannabinoid receptor type 1 and cannabinoid receptor type 2 in the central and peripheral nervous system. They are also present in nmol L(-1) concentrations in human blood plasma; however, their association with possible molecular carriers remains poorly characterized. Here we report on the quantification of 46 endogenous molecular species from five major classes of endocannabinoids and endocannabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…For most compounds, concentrations measured in the present study were in close agreement with those previously reported by our group 6 and others. 7 PEA levels were similar to those reported by Bilgin et al 18 and by Sipe et al, 19 but 10 to 20 times higher than those reported by other groups 7–17 and previously by us. 6 This suggested that a contamination might be present.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…For most compounds, concentrations measured in the present study were in close agreement with those previously reported by our group 6 and others. 7 PEA levels were similar to those reported by Bilgin et al 18 and by Sipe et al, 19 but 10 to 20 times higher than those reported by other groups 7–17 and previously by us. 6 This suggested that a contamination might be present.…”
Section: Resultssupporting
confidence: 90%
“…6,7,12,13,16,17 Regarding absolute values, two separate laboratories reported levels of PEA and OEA in plasma that were excessively high, 18,19 which reached or exceeded the concentrations needed by these ligands to engage PPAR-α as agonists. PEA and OEA are, in fact, considered high-potency ligands of PPAR-α; in heterologous expression systems, these FAEs engage the receptor with median effective concentration (EC 50 ) values of 0.12 μM for OEA and 3 μM for PEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By LC-MS/MS on a triple quadrupole mass spectrometer TSQ Vantage (Thermo Fisher Scientific, San Jose CA) was performed as described22 with minor modifications; MRM transitions and instrument settings are in Supplementary Table S1. NAAsp were quantified by external calibration using unlabeled synthetic compounds.…”
Section: Methodsmentioning
confidence: 99%
“…To compensate matrix effects standards were spiked into a rat tissue extract in which NAAsp were undetectable. Comparative profiling of NAE by the method of PRM on a hybrid quadrupole – Orbitrap tandem mass spectrometer Q Exactive (Thermo Fisher Scientific) was performed as described22 using inclusion list of precursor m/z (Supplementary Table S1). Rat tissues were obtained from licensed Biomedical Services Facility (MPI of Molecular Cell Biology and Genetics, Dresden).…”
Section: Methodsmentioning
confidence: 99%